The Economic Values of Pancasila in the Local Wisdom of Harvesting Rice at Kampung Naga - Jarot Tri Bowo Santoso (Universitas Negeri Malang, 2021)
This research aims to explore the economic values of Pancasila in the local wisdom of harvesting rice in Kampung Naga, Tasikmalaya, West Java. An ethnographic type of qualitative research is conducted in Kampung Naga, Neglasari Village, Salawu District, Tasikmalaya Regency of West Java. The informants of this research are 20 people consisting of the head of the custom, head of the cooperative association, and farmers in Kampung Naga. The data are collected using in-depth interviews. They are then analyzed using data triangulation, including data reduction, presentation, and conclusions are drawn. The results show that the economic values of Pancasila in the local wisdom of harvesting rice in Kampung Naga are classified into practical value, the cost-saving value of harvesting, economic equity value, and the value of increasing income. Keywords: Economic values of Pancasila, Cost-saving harvesting, Local wisdom, Economic EquityJEL Classification: D40, I30